2020
DOI: 10.1097/scs.0000000000006238
|View full text |Cite
|
Sign up to set email alerts
|

The Preliminary Application of Augmented Reality in Unilateral Orbitozygomatic Maxillary Complex Fractures Treatment

Abstract: Purpose: Try to apply augmented reality (AR) technique which based on visual recognition artificial marks in the treatment of unilateral Orbitozygomatic Maxillary complex fractures (OZMF), and to explore the feasibility and the application value of the AR for assisting the oral and maxillofacial surgery (OMFS) treatment. Methods: Based on the AR application JSARToolKit developed on the web, and combining with the self-designed tooth-borne type visual re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…This experiment is a single-center prospective randomized controlled trial. Because this kind of experiment has not been carried out previously, the calculated number of samples mainly refers to the previously related published literature [ 20 24 ]. With the approval of the ethics committee, the number of patients in each group needs to be 10 for the primary outcome to be statistically significant; meaning a total of 20 patients is needed.…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…This experiment is a single-center prospective randomized controlled trial. Because this kind of experiment has not been carried out previously, the calculated number of samples mainly refers to the previously related published literature [ 20 24 ]. With the approval of the ethics committee, the number of patients in each group needs to be 10 for the primary outcome to be statistically significant; meaning a total of 20 patients is needed.…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%
“…Similar studies have demonstrated the efficacy of the AR system in treating hemifacial microsomia [ 20 ], orbital hypertelorism [ 21 ], craniosynostosis [ 22 ], and craniofacial contouring surgery [ 23 ]. While there was a study on the application of AR to the treatment of unilateral orbitozygomatic maxillary complex fracture [ 24 ], it was a single-arm study with small sample size. Thus, the purpose of this randomized controlled study is to evaluate the efficacy and safety of AR system in treatment with craniofacial fracture reduction.…”
Section: Introductionmentioning
confidence: 99%
“…1D). Although keeping the relative spatial coordinates unchanged, the patient's reconstructed nose model, and the artificial marker were imported into the HuaxiAR1.0 software system developed and built by the research group in the early stage 2 …”
Section: Methodsmentioning
confidence: 99%
“…presents the full, tabulated data set on surgical outcomes in maxillofacial surgery, while TableA14tabulates the data on the technology used. Two studies were identified in maxillofacial surgery: a case series on nine patients undergoing AR-guided repair of facial fracture, and a series of five patients undergoing MR-guided recontouring surgery for craniofacial fibrous dysplasia 101. Liu et al reported a series of five patients undergoing MR-guided recontouring surgeries for craniofacial fibrous dysplasia.…”
mentioning
confidence: 99%